El hijo de la montaña: Proceso de investigación y creación para la producción de un EP de Hip-Hop latino (2024)
The objective of this project is the production of a hip-hop double single in collaboration with the Bogotan rapper Benji Piolet. It was developed through a co-authoring process where different aesthetic parameters were proposed, which, aided by research, led to a product with an innovative vision. A methodology of research and creation was employed, as through critical listening and analysis of genre-referent producers, techniques for beat creation, creative decision-making, mixing, among other factors, were enriched, leading two phonograms to a high-quality standard.